Trudy - Anderson, Jessica, 1916-2010. (Minneapolis, Minn. : Milkweed Editions, 2005)
Twelve-year-old Trudy's life is filled with changes, mainly centered around starting middle school, and as she struggles to take them all in stride she is hit with the biggest change of all--her elderly father's diagnosis of dementia.
Keywords: Change -- Fiction; Old age -- Fiction; Middle schools -- Fiction; Families -- Texas -- Fiction; Schools -- Fiction; Alzheimer's disease -- Fiction; Texas -- Fiction